1981
DOI: 10.1136/oem.38.4.339
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory function in workers exposed to tea and wood dust.

Abstract: Changes in ventilatory capacity during the work shift were studied in workers exposed to tea dust in two tea-packing plants, wood dust in two furniture factories, and virtually no dust in an inoperational power station. The FEV, and FVC in workers exposed to dust were found to decline during the work shift by a small but significant volume. The MMFR, Vmax 50% and Vmax 75%were too variable to display any trend. No dose-response relationship could be discerned between the fall in workers' ventilatory capacity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 24 publications
3
18
0
Order By: Relevance
“…Liou et al (1996) demonstrated that the pulmonary function parameters MMF, PEFR, and FEF 25% were significantly lower in the exposed workers than in controls for both smokers and non-smokers and also showed a declining trend with increasing exposure levels. Similarly, Al Zuhair et al (1981), Holness et al (1985), Carosso et al (1987), Herbert et al (1995), and Schlunssen et al (2002) showed a cross-shift decrease in forced expiratory volume in one second (FEV 1 ) among wood workers.…”
Section: S a Meomentioning
confidence: 87%
“…Liou et al (1996) demonstrated that the pulmonary function parameters MMF, PEFR, and FEF 25% were significantly lower in the exposed workers than in controls for both smokers and non-smokers and also showed a declining trend with increasing exposure levels. Similarly, Al Zuhair et al (1981), Holness et al (1985), Carosso et al (1987), Herbert et al (1995), and Schlunssen et al (2002) showed a cross-shift decrease in forced expiratory volume in one second (FEV 1 ) among wood workers.…”
Section: S a Meomentioning
confidence: 87%
“…Occupational exposure to wood dust has been well documented as a cause of adenocarcinoma of the nasal and paranasal sinuses [Acheson et al, 1968;Franklin, 1982;IARC, 1995;Ironside and Matthews, 1975;Leclerc et al, 1994], mucostasis [Wilhelmsson and Drettner, 1984], eye and skin irritation [Woods and Calnan, 1976], rhinitis and asthma [Enarson and Chan-Yeung, 1990;Gandevia and Milne, 1970], deterioration of respiratory effects [Al Zuhair et al, 1981;Carrosso et al, 1987;Goldsmith and Shy, 1988;Rastogi et al, 1989;Shamssain, 1992;Whitehead et al, 1981], and fibrosis of the lungs [Michaels, 1967]. Previous studies have reported dose-response relationships between respiratory function and dust exposure among woodworkers [Holness et al, 1985;Liou et al, 1996].…”
Section: Introductionmentioning
confidence: 97%
“…There is no evidence that any other variable would have correlated with amplitude but is excluded from the regression because of its relationship with variables already selected. Accord- Table 3 Amplitude and acrophase (time ofday) ofthe circadian rhythm in peak expiratory flow rate in groups of participants selected according to various criteria (p < 0.001 for all rhythms) [14][15][16][17][18][19][20] Symptom free office staff Cinkotai, Sharpe, Gibbs ing to the Mann-Whitney non-parametric test (table 4) the mean amplitude in cotton workers claiming to suffer from bronchitic symptoms was significantly higher than their symptom free counterparts (p < 0.04), as was the amplitude in older cotton workers compared with that of their younger colleagues (p < 0-02). The mean amplitude in female cotton workers was higher than in men but this difference was not significant.…”
Section: Factors Associated With the Pefr Rhythmmentioning
confidence: 99%